Corporate social responsibility – An idealistic goal or a reality? - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Despite widespread discussion on CSR, there continues to be much disagreement around what constitutes CSR, and how to define it. In addition, the term is often used interchangeably with notions such as corporate responsibility, corporate citizenship, triple-bottom line, sustainability, creating shared value, and in some cases, corporate ethics and governance. However, all of these ideas point in the same direction: a sharp escalation in the social roles corporations are expected to play today.